Pengenalan Potensi UMKM Gula Merah dengan Kemasan Gula Semut dan Gula Batu di Desa Barambang, Kec. Sinjai Borong, Kab. Sinjai Melalui Video Dokumenter - Rahmatullah Rahmatullah; Sartika Sartika; Rifkah Damayanti Abduh; Andi Elfira Yusria; Dielci Maryam Virginia; Fajar Abdillah; Resky Aulia M; Muhammad Dzakwan Zhafran; Muhammad Alisofyan Ar Djambia; Kasma N; Umar Sabirin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The implementation of KKN is contained in the third point of the Tri Dharma of higher education. This is intended so that students can gain knowledge that is not available on campus. Apart from that, students also carry out community empowerment and service in their work areas from the knowledge they have gained on campus. The aim of this